The Analysis and Critique of Book of ‘Iran from the Early Islamic ra to Mongol Invasion’ - Hamid Karamipour (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The author of this book, Dr. AliAkbar Velayati, has examined Iranian history from the advent of Islam to Mongol invasion in ten chapters. As it is characterized from the titles of chapters of the book, this work has referred to Iranian political history during aforementioned period, and economic and social issues have been dispersedly discussed. The book’s author has shown his religious and value-driven interests even in description of events and taken his own specific approach in discussing reasons of events by enjoying historic texts. The important point is that an ideological attitude governs heavily over all chapters of the book so that Shiite and related teachings have been turned into the major discourse of Iranian nation in all historic eras. Regarding critique and analysis of this study, it is tried to reveal how much the author has been abided by research principles of historic knowledge whether by method or by content.